(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
NGO is the most important servingsector in India. It is the prime mover of Indian society. Funding problem,political interference political problem, interference from other NGOs, lack ofdevoted manpower, co-option of NGOs by Government is very bed for the sector.Keeping constant updates from micro to macro is very difficult being in thefield. It is not providing only food, shelter and clothes for needy persons ofthe nation with a population of 102.7 crore in 2001 and employment for millionbut it is also a source of providing justice for the weaker section of thecountry. It is the main source of transferring services from rich to poorhealthy to needy and publicly enforcement of efforts in the favour of those whoare not able to put their efforts for moving in the country. NGOs are alsoprovided their services in the field of water arrangements, tree - plantation,sanitary/sanitation, sports and also do awareness among people. But, thequestion arises that the NGOs are satisfying themselves through these servicesand what types of problems they are facing actually? To answer these questions,a study entitled "Role of Non-Governmental Organization in India-AnEvaluation of District Sirsa" has been conducted to evaluate theperformance of Non-Governmental Organizations in India.